The evolution of cutting technology and metal-cutting machines in the paradigm of technological modes - A. P. Kuznetsov (Ekonomika Nauki)
The article examines, from a historically foreseeable perspective, the technological methods of cutting and metal-cutting machines based on available literature. It summarizes and systematizes the directions and achievements of scientific research on cutting theory, as well as the creation of machine tools and their level of perfection. The goal of the study is to demonstrate, through the evidence from metal cutting machines, the significance and effectiveness of changes in economic development in relation to the technological mode. Using systems analysis, the level of development can be assessed based on the normative value of resource efficiency, which measures how well technology indicators are achieved through the design of machines and technological equipment. Factors that influence the formation of these indicators depend on technical and technological conditions and aim to achieve maximum values based on the technological capabilities for their implementation in industry and economy.